A Development of Educational Assembly Model to Promote People Participation - Siribanpitak, Pruet; Kijtorntham, Wichuda (Scholar: Human Sciences, 2016)
The objectives of this research were 1) to design and develop the educational assembly model 2) to test and improve the designed educational assembly model and 3) to propose policy implication for implementing the educational assembly model to promote people participation in educational provision. The designed educational assembly model was examined by experts and stakeholders and tested at the provincial level in eight provinces. The findings revealed that the “Triple Three Educational Assembly Model: 333 Model” was an essential add appropriate tool to promote people participation in education. The first “Three” refers to three levels of educational assembly comprise of the provincial level, the provincial cluster level, and the national level. The second “Three” refers to three components of educational assembly comprise of knowledge sector, people sector, and government sector. The third “Three” refers to three key activities comprise of knowledge research and development, assembly meeting, and monitoring of meeting resolutions. The research suggested that he Office of Education Council should set up a task force for the implementation of the educational assembly to promote people participation in educational provision